From ideologies, to institutions, to punishment: the importance of political ideologies to the political economy of punishment - Gallo, Zelia A. (Tracing the relationship between inequality, crime, and punishment, 2020)
This chapter argues that institutionalist accounts of punishment, crime, and inequality should look to the thinning of political ideologies and its institutional implications. It explores the claim according to which thin ideologies such as populism, technocracy and plebiscitarianism, have institutional ambitions and tend to incentivise reforms that favour executive discretion and a politics of disintermediation. This claim is illustrated by reference to Italy both during and after the Eurozone crisis. Italy functions as a starting point for a broader discussion of how ideologies might change institutions, and therefore the penal incentives that follow from particular institutional configurations. The chapter argues that institutional changes rooted in thin ideologies may have long-term effects on punishment by incentivising a more adversarial and retaliatory approach to conflict - and thence to crime and deviance - and dis-incentivising a more negotiated and reintegrative approach to conflict, including the type of interpersonal conflict represented by crime and deviance.